Reflexões sobre a política de descentralização em saúde: uma análise a partir do Hospital Monsenhor Walfredo Gurgel em Natal (RN) - Pereira, Maria Cristina Silva (2010)
The process of decentralization of health policy in Brazil has evolved throughout the second half of the twentieth century, advancing by leaps and bounds in the last two decades. The various public institutions have assumed the function of responding to a growing demand for medical care and hospital. Monsenhor Hospital Walfredo Gurgel - H.M.W.G. fits into this context as an institution par excellence-oriented service the demand for medium and high complexity. This paper presents some questions about the process of decentralization and devolution occurred in Brazil. To do so is a brief historical background and politics, showing the concepts of reform and counter-reform and how the processes mentioned in the Country Correlates develop local social development of the decentralization process and discusses the modifications in policies social intervention in recent decades and the state health policies. Presents the implementation of a Health System in Brazil and the state showing how the decentralization of health policy occurs in Rio Grande do Norte. Finally, it explores the role of H.M.W.G. in health policy in RN. For this, portrays the institution and is located within the decentralized structure of health policy in the state and capital. An analysis of the demand for hospital care and the budget situation is realized at the close of work, correlating the role of HMWG with the decentralization of health policy in Brazil and Rio Grande do Norte. The methodology used for the preparation of this work was based on documentary research, systematic nonparticipant observation, field diary and analysis of data, documents and content. This set shows a quantitative and qualitative methodology that strips the institution, enabling the understanding of their role, boundaries, threats and opportunities